An Approach To Mitigate The Narrowband Jamming in DSSS-CDMA System - Manna, Tanajit; Sengupta, Subhradeep; Kole, Alok (International Journal of Computer Sciences and Engineering, 2025)
A cost effective approach for better communication to mitigate the narrow band jamming in Code Division Multiple Access (CDMA) system in case of Direct Sequence Spread Spectrum (DSSS) single user system is depicted in the paper. The need for improvement of the jamming problem in modern telecommunication system has huge applications in security sector. A comparative analysis of Power Spectral Density (PSD) of CDMA with and without narrowband jamming condition is proposed in this paper. By variation of signal power and Barker code, an optimised system is illustrated supported by Bit Error Rate (BER) and Signal to Noise Ratio (Eb/N) curve. Increment of signal power provides us low narrowband jamming as well as jamming free PSD. Spreading factor variations supported by Barker Code illustrates the results in favour of optimization of the system under narrow band jamming condition. The entire above spoken CDMA-DSSS system modelling and performance analysis are implemented using MATLAB.